(untitled) (Fiep Bulletin - online, 2017)
The training of university teachers is a subject of ongoing debate and research, since it means the possibility ofpromoting education professionals trained to meet the new challenges of the knowledge society and speed of information.The work presented, exposes a set of interrelated criteria to deepen into the search of quality in the current processes oftraining of university teachers.